Analisis Hubungan Masa Kerja terhadap Gangguan Fungsi Pendengaran pada Pekerja Tambang Batu Bara - Ilham Rahmatullah; Apriyani; Rinda Purwanto (Faletehan Health Journal, 2025)
Hearing loss due to noise exposure is a significant health problem, especially in high-noise work environments, such as the coal mining industry. This study aims to analyze the effects of length of employment on hearing impairment among workers at X Inc., Bontang. A quantitative approach with a cross-sectional method was used in this study, involving 52 workers who were exposed to high noise in the geology, CHP, utilities, and port facility operation area. Data collection was carried out through an audiometric survey to measure the level of hearing loss at various frequencies. The results showed that most respondents (86.5%) were over 40 years old and had worked for more than 10 years, leading to higher risk of hearing loss. Additionally, the relationship between length of employment and rate of hearing loss was significant; coal miners who worked longer showed more severe hearing loss. This study suggested the importance of implementing stricter noise regulations and more effective health protection to prevent hearing loss among coal miners. These findings can provide a basis for policymakers to formulate better preventive measures.